1997
DOI: 10.1109/4.553171
|View full text |Cite
|
Sign up to set email alerts
|

Delta-sigma modulators using frequency-modulated intermediate values

Abstract: This paper describes a new first-and second-order delta-sigma modulator concept where the first integrator is extracted and implemented by a frequency modulator with the modulating signal as the input. The result is a simple delta-sigma modulator with no need for digital-to-analog converters, allowing straightforward multi-bit quantization. Without the frequency modulator, the circuit becomes a frequency-to-digital converter with delta-sigma noise shaping. An experimental first-and second-order modulator have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
119
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(124 citation statements)
references
References 10 publications
0
119
0
Order By: Relevance
“…It can be shown that multiple taps improve the signal-toquantization-noise (SQNR) of the digital version of θ(t) in proportion to the number of taps used [3]. For a first-order single-bit modulator using m taps, the SQNR is given by [3] SQN…”
Section: Improved Fdsm Designsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be shown that multiple taps improve the signal-toquantization-noise (SQNR) of the digital version of θ(t) in proportion to the number of taps used [3]. For a first-order single-bit modulator using m taps, the SQNR is given by [3] SQN…”
Section: Improved Fdsm Designsmentioning
confidence: 99%
“…In the FDSM, the input signal v in (t) is first integrated by the RVCO, which encodes the signal in the phase θ(t) of the oscillation waveform, since θ(t) is given by [3] θ(t) = 2π…”
Section: σ∆ Modulator With Intermediate Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…A frequency ΔΣ converter (FDSM) is a ΔΣ converter without feedback [1]. The feedback in a ΔΣ converter can be eliminated by building a system consisting of an integrator and a differentiator.…”
Section: Introductionmentioning
confidence: 99%
“…However, its use is restricted to relatively low frequency applications due to the limitation of the sampling frequency. The DSM using frequency modulated intermediate signal (FMDSM) [2,3,4] has significant advantages that it has no feedback digital-analog converter (DAC) restricting the operation frequency, and hence, is suitable for high frequency operation. However, the FMDSM has been not widely used so far, since it is difficult to apply the FMDSM concept to higher order DSMs.…”
Section: Introductionmentioning
confidence: 99%